The attitude of Polish consumers to organic food - Wojciechowska-Solis, Julia; Soroka, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the study was to determine the requirements for organic food expected by Polish consumers. A method of diagnostic survey was used in the study with the author’s research tool in the form of a survey questionnaire. The sample consisted of 1102 respondents. The Statistica 10.1 PL program was used for statistical analysis, including the analysis of discriminant function. The production of organic food should take place naturally without harmful substances. In Poland, the organic production has the potential to produce high protein and micronutrient products as well as of a reduced toxin contamination. The main places to purchase organic food were discount stores and those specializing in selling organic food as well as organic farms. It was emphasized that the respondents placed great importance on the accreditation of the product certification body on food packaging as well as on labeling these products as produced in ecological conditions. Currently the organic food market is considered to be a niche, but its importance is steadily increasing
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 475, s. 380-389
Keywords: organic food; consumption; niche market; żywność ekologiczna; konsumpcja; rynek niszowy